Recherche littéraire / Literary Research Automne / Fall 2021 - Maufort, Marc (Recherche littéraire / Literary Research, 2021)
Franca Bellarsi Olga Beloborodova Lidia Morales Benito Jean Bessière Eury Colin Chang Véronique Corinus Santanu Das Subhraleena Deka Elke D'hoker Brahim El Guabli Marlene Hansen Esplin Massimo Fusillo Claudio Gigante Gerald Gillespie Stefan Helgesson Yvon Houssais Višnja Krstić Marie Laureillard Marc MaufortYana Meerzon Kai Mikkonen Florian Mussgnug Anzazi Joan Mwangovya Birgit Neumann Wen-chin Ouyang Daniel-Henri Pageaux Yolaine Parisot Danielle Perrot-Corpet Yannick Preumont E.V.Ramakrishnan Hubert Roland Karen-Margrethe Simonsen Vijaya Singh Daria Tunca Dirk Van Hulle Roberto Vecchi Cyril Vettorato Luke Walker Jenny Webb Robert J.C. Young.